Electromechanical modeling by DEM for assessing internal ball bearing loading. (October 2015) - Machado, C.; Guessasma, M.; Bellenger, E.
Abstract: A numerical approach makes electrical measurements in a rotating ball bearing, in order to characterize the loading state of the bearing and to detect any defects. The ball bearing is modeled by discrete elements with a smoothed formulation of the local contact law. Contact forces are calculated using analogies with damped springs. Loads in accordance with the practice case are applied to the bearing. The electrical resistance of the contact is evaluated in an electromechanical model using Hertz's surfaces. The results show a link between the mechanical state of the bearing and the electrical measurement. Highlights: A ball bearing is modeled with the DEM. The mechanical results are compared with manufacturer's analytical approach. An electromechanical coupling is proposed. The internal loading is evaluated using an electrical resistance measurement.